Transformasi Pelayanan Pastoral di Era Disrupsi: Model Jejaring dan Trauma-Informed Care bagi Jemaat Kawasan Industri - prayveenrenalchris (Unit Penerbitan Informasi dan Teknologi Sekolah Tinggi Teologi Gereja Kalimantan Evangelis (STT GKE), 2026)
This study discusses the pastoral counseling model in the GKST industrial area. Industrialization in the GKST area, particularly in Morowali and North Morowali, has caused profound social disruption, putting pressure on workers. As a result, cases of suicide and mental health disorders among workers have increased. Pastoral counseling provided by churches, particularly pastors, still does not reach enough workers. This study uses a descriptive qualitative method with data collection through in-depth interviews with pastors and related document studies. The results of the study identify three main realities: dependence on face-to-face counseling models, a shift in relationship patterns from agrarian to industrial, and a weakening of communal togetherness. As a solution, this study offers a networked relational support model, which integrates a hybrid approach (online and offline), empowers congregations as “Supporting Friends,” and applies the principles of Trauma-Informed Care. This model transforms the role of pastors from sole responsible parties to network facilitators, enabling churches to function as safe spaces and recovery networks that are more adaptive, far-reaching, and relevant in this era of disruption.